The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1177/0885728811427157
|View full text |Cite
|
Sign up to set email alerts
|

Individual Skill Predictors of the School- and Career-Related Adjustment of Adolescents With Disabilities

Abstract: In this investigation, the authors examine the relationship between individual skills (i.e., career locus of control [LOC], social skills [SOC], and social problem–solving skills [SPSS]) and the school- and perceived career–related adjustment of 211 students with disabilities. Data pertaining to individual skills were gathered from student reports, and data pertaining to adjustment were gathered from student and teacher perceptions. Results of hierarchical regression analyses indicated that together LOC, SOC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Although we have anticipated similar associations between the key variables (self-efficacy and expected outcomes) involved in choosing a high school major, as found among adolescents without LD (Brown & Cinamon, 2014), the unique challenges and consistently reported low self-beliefs characteristic of adolescents with LD (Pinkney et al, 2012) raise an important question regarding the factors impacting these variables.…”
Section: Self-efficacy and Outcomes Expectations For Selecting A Highmentioning
confidence: 63%
See 2 more Smart Citations
“…Although we have anticipated similar associations between the key variables (self-efficacy and expected outcomes) involved in choosing a high school major, as found among adolescents without LD (Brown & Cinamon, 2014), the unique challenges and consistently reported low self-beliefs characteristic of adolescents with LD (Pinkney et al, 2012) raise an important question regarding the factors impacting these variables.…”
Section: Self-efficacy and Outcomes Expectations For Selecting A Highmentioning
confidence: 63%
“…Studies on the career decision-making process of adolescents with LD are ambiguous; most studies have characterized them as having poorer decision-making skills, lower levels of self-efficacy in making vocational decisions, lower career outcome expectations, and poorer vocational identities, compared with their normative peers (see Lusk & Cook, 2009; Pinkney et al, 2012; Solberg et al, 2012). However, other studies have indicated that many students with LD successfully graduate from higher education institutions and report high or similar self-perceptions, in comparison with their normative peers (Blake & Rust, 2002; Talmor & Kayam, 2006).…”
Section: Career Development Of High School Students With Ldmentioning
confidence: 99%
See 1 more Smart Citation
“…The commitment to understand and provide the essential needs and support the students physically, socially and also emotionally were important component to build healthy work environment for the students' well-being. As Pinkney, Murray, and Lind (2012) suggested that to improve student functioning across multiple context, individual skills that are predictive of functioning across multiple domains should be focused during the training session.…”
Section: Discussionmentioning
confidence: 99%
“…Data collected about social-emotional and adaptive behavior functioning are equally relevant to transition planning. Strong interpersonal skills among IWD, for example, are highly valued by employers (Ju, Zhang & Pacha, 2012) and are associated with good work habits and higher rates of employment (Benz,Yovanoff & Doren, 1997;Pinkney, Murray & Lind, 2012). Further, certain behavior patterns and personality attributes tend to predict success in life.…”
Section: The Relevance Of Psycho-educational Datamentioning
confidence: 99%